FUNCTIONAL OUTCOMES AND ASSOCIATED FACTORS AFTER PROXIMAL FEMORAL NAIL ANTIROTATION FIXATION FOR INTERTROCHANTERIC FEMORAL FRACTURES (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate hip functional outcomes using the Harris Hip Score (HHS) and to investigate associations between selected clinical factors, fracture characteristics, radiographic features, and functional outcomes in patients with intertrochanteric femoral fractures treated with proximal femoral nail antirotation fixation.Subjects and methods: This descriptive retrospective-prospective study included 36 patients with intertrochanteric femoral fractures who underwent surgical fixation using proximal femoral nail antirotation. HHS was assessed at the 6-month postoperative follow-up and compared according to age, sex, comorbidities, mechanism of injury, AO fracture classification, and selected radiographic characteristics. The t-test, ANOVA, Chi-square test, or Fisher's exact test was used as appropriate, with statistical significance set at p < 0.05.Results: The Harris Hip Score differed significantly according to age group and sex in univariate analysis. The mean HHS showed a decreasing trend with increasing age, from 94.71 ± 3.68 in patients aged
Keywords: Intertrochanteric femoral fracture, proximal femoral nail antirotation, Harris Hip Score, associated factors.